The Wine as a research object in the areas of Tourism and Administration: a bibliometric perspective from the Spell and Web of science - Pedroso Teixeira, Renan; Ferro, Rafael (RITUR - Revista Iberoamericana de Turismo, 2023)
Because of the importance of wine for societies, this article aimed to map and characterize the scientific production in the format of articles published in journals of Tourism and/or Hospitality and Administration that have wine as an object of study. This research has a quantiqualitative approach and is explorative and descriptive. The search terms "wine*" and "wine*" were applied respectively in the Spell and Web of Science databases. After applying search filters and relevance analysis, a national corpus of 46 articles and an international corpus of 163 articles were defined. In addition, we sought to identify the recurring themes in this research through thematic analysis and keyword correlation. The international scientific production has a larger number of researchers, journals, and themes than the national production. However, despite being more representative in terms of the total number of articles analyzed, the international scientific production has shown itself to be in a state of plateau in its temporal evolution, while the national scenario is in relative growth. The lack of studies that relate wine to the concepts of hospitality and hospitality is also noteworthy. At the end of the article, we present some propositions for future studies that focus on the beverage.